(3GdLed aj GdEYQGHs - (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s ((3eMeO Hf CHj GdaVd GdUGjZi GdHjgbi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeO GdTGcQjf gPg Led QJHJgG JQJjHkG bQjH GdeJfGhd hLYdJgG NeSI aUhd GdaUd GdChd ai GdebOeGJ s
(3BNQgG (B:s
(3HGH GdeaQO hGdLedI EYde Cf GdhGMO ef GdGSe hGdaUd hGdMQha jSei cdeI de jLRC hcPG GdHGbi agPG BNQ eG CQOfG ef GdLed ai YhGed GdEYQGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B310 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B606s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B602s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs